Phytophthora urerae sp. nov., a new clade 1c relative of the Irish famine pathogen Phytophthora infestans from South America - Grunwald, N.J.; Forbes, G.; Pérez, W.; Stewart, J.E.; Fieland, V.J.; Larsen, M.M. (Wiley, 2019)
An unknown Phytophthora species was discovered in the central Peruvian Andes on blighted foliage of the native South American plant species Urera lacineata. Urera is a genus of native flowering shrubs in the nettle family Urticaceae. This new taxon Phytophthora urerae sp. nov. is herewith formally described based on extensive morphological analysis, phylogenetic analysis of nuclear and mitochondrial loci, and AFLP analysis. Phytophthora urerae sp. nov. is a close relative of the Irish famine pathogen, Phytophthora infestans, and only the third clade 1c taxon described from South America to date. In contrast to the clade 1c taxon Phytophthora andina, first described in South America as a hybrid, P. urerae does not appear to be a hybrid based on cloning and sequencing nuclear loci. Findings of new species in South America may provide novel insights into the origin and evolutionary history of clade 1c Phytophthora species.